From Basel I to Basel III : Sequencing Implementation in Developing Economies - Ferreira, Caio.; Jenkinson, Nigel; Wilson, Christopher (Washington, D.C. : International Monetary Fund, 2019)
Developing economies can strengthen their financial systems by implementing the main elements of global regulatory reform. But to build an effective prudential framework, they may need to adapt international standards taking into account the sophistication and size of their financial institutions, the relevance of different financial operations in their market, the granularity of information available and the capacity of their supervisors. Under a proportionate application of the Basel standards, smaller institutions with less complex business models would be subject to a simpler regulatory framework that enhances the resilience of the financial sector without generating disproportionate compliance costs. This paper provides guidance on how non-Basel Committee member countries could incorporate banks' capital and liquidity standards into their framework. It builds on the experience gained by the authors in the course of their work in providing technical assistance on-and assessing compliance with-international standards in banking supervision.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet